Increasing the competitiveness of Ukrainian livestock products within the development of the post-industrial circular green economy model - Perehuda, Yuliia (Management and Entrepreneurship: Trends of Development, 2024)
The article is dedicated to developing new scientific solutions to enhance the competitiveness of Ukrainian livestock products in the context of developing the post-industrial circular green economy model. The article has proven that Ukrainian livestock enterprises have significant opportunities to increase production and sales, both on national and global (foreign) markets, due to enhancing the competitiveness of their products, taking into account the features of transitioning to a post-industrial circular green development model. The article aims to identify differences in the external and internal environments of livestock enterprises and develop measures to increase livestock products' competitiveness during the transition to a post-industrial circular green model of development. Methodology: a set of general and special methods was used at empirical and theoretical levels, including historical and comparative assessments for evaluating global, international, and national economic systems transitioning to a post-industrial circular green development model; comparison to provide a description of the development models of livestock enterprises within the framework of forming the competitiveness of products according to the parameters of the internal and external environment; logical generalization and scientific abstraction for developing a set of measures to increase the competitiveness of livestock products when transitioning to a post-industrial circular green development model of domestic livestock enterprises; methods of systematization, grouping, and logical generalization for systematization of information, formation of conclusions and scientific proposals of the article. The article uses system-functional, historical, and systemic approaches to reveal and solve the problems of increasing the competitiveness of Ukrainian livestock products in the conditions of developing the post-industrial circular green model of the economy. Results: a set of measures to increase the competitiveness of Ukrainian livestock production during the transition to a post-industrial circular green development model was formed. JEL Classification: О13, Q10